Going Beyond NCAA Bylaw 5-1-(j): Developing Learning Prescriptions for Student-Athletes - Bruno, James E.; Holland, Judith R.; Ward, Joseph W. (My University, 1987)
In recent years academic support programs for the student-athlete have become an integral component of athletic departments at major colleges and universities. This study reports the use of a test-scoring procedure called Modified Confidence Weighted-Admissible Probability Measurement (MCW-APM) to assist athletic department academic support personnel in diagnosing student-athlete knowledge gaps. A series of nine criterion-referenced tests (CRT) in fundamental knowledge-base areas of mathematics, language arts, and reading at the elementary, secondary and junior college skill levels was administered to a group of freshmen student athletes at UCLA. The MCW-APM test-scoring analysis generated specific learning prescriptions for each student-athlete along with information usecognitive maps to indicate those knowledge-base areas where the student-athlete was informed, partially informed, uninformed, or misinformed. The learning prescription was then used by the tutorial program staff for developing an individualized instruction plan. Subsequent clustering of student-athletes by information type was used to design courses, workshops, and special programs with instructional objectives towards reeducation (for misinformed areas), instruction (for areas with lack of information) and review (for areas with partial information).
Keywords: academic support; skills; academic predictors